Strategies for Strengthening Children's Reading Interest in the Digital Age through Early Literacy: A Systematic Review - Furbani, Widiastuti (MSJ : Majority Science Journal, 2025)
The development of digital technology has a significant impact on children's behavior and habits in accessing information and entertainment, including reading. On the one hand, easy access to various digital reading resources is a great potential to improve reading literacy from an early age. But on the other hand, the presence of digital media also poses serious challenges to children's interest in reading due to competition with instant and visual entertainment content. This journal aims to examine effective strategies and approaches in fostering children's interest in reading in the digital era by developing early reading literacy. The method used is a Systematic Literature Review of various studies, scientific articles, and empirical data that discuss children's literacy, digital media use, and educational approaches that are adaptive to changing times. The results show that the integration of technology with creative reading learning methods, family and school support, and the availability of interesting and age-appropriate reading materials are key factors in shaping children's reading habits. In conclusion, fostering children's interest in reading in the digital era requires a multidisciplinary approach that synergizes education, technology, developmental psychology, and public policies that support a culture of literacy.